Membaca untuk Memahami bukan Bersenandung: Pemahaman atas QS. al-Furqān [25]: 30-33 perspektif Ma’nā-cum-Maghzā - Kumalasari, Aidah Mega (Sunan Kalijaga Islamic State University, 2023)
The practice of reciting the Qur'an rhythmically and slowly, as indicated by the term rattalnahu tartīlan, has sparked significant debate regarding the balance between understanding and aesthetic beauty. This research seeks to uncover the historical meaning of this term by examining the broader context of the verses. Specifically, the study focuses on QS. al-Furqan [25]:30-33, analyzed through the ma'nā-cum-maghzā approach. The findings reveal that rattalnahu tartīlan is a small yet integral part of the verse's response to the accusations made by the Quraysh of Makkah against the Prophet's mission. The Quraysh's habit of making unreasonable demands to undermine the Prophet is reflected in this context, particularly concerning the gradual revelation of the Qur'an. The term rattalnahu tartīlan signifies the method used to embed the Qur'an's content into the Prophet's heart, justifying its gradual revelation. The derogatory claim, linked to the use of the term mahjurā, is found exclusively in verses revealed before the Hijrah (Makkiyah). God's response to the Quraysh's persistent pressure, which troubled the Prophet, is a declaration that opposition is inevitable for every Prophet. The opposition from the Prophet's enemies was met with a truthful and clear response from God, encapsulated in the overall message of QS. al-Furqan [25]:30-33, which serves to bring peace to the Prophet Muhammad.